THE LONG-DRAWN-OUT FREE TRADE AGREEMENT NEGOTIATIONS BETWEEN THE EUROPEAN UNION AND INDIA: A TWO-LEVEL GAME ANALYSIS - Yusuf Gökhan Atak (Ankara Avrupa Çalışmaları Dergisi)
This article examines the arduous free trade agreement negotiations between the European Union and India. The talks, which started in 2006 and were suspended for a while, could not lead to an agreement in more than 15 years. By employing the two-level game theory, developed by Robert Putnam, this article attempts to explore the role of the domestic realm on the extension of the negotiations. Therefore, itinvestigates the win-sets of the negotiating parties, by focusing on the domestic factors such as interest groups, political structure and political culture in order to determine which of these factors make it difficult to find common ground. On the basis of the said analysis regarding the free trade agreement negotiations between the European Union and India, this article further aims at finding out why tradenegotiations pursued by the European Union usually require a long period of time.